Knowledge, Safety, and Meta‐Epistemic Belief. (7th June 2018) - Ross, Jacob
Abstract: This article raises problems both for the view that safe belief is necessary for knowledge and for the view that it is sufficient. Focusing on 'meta‐epistemic beliefs, ' or beliefs about the epistemic status of one's own beliefs, it is shown that the necessity claim has counterintuitive implications and that the sufficiency claim implies a contradiction. It is then shown that meta‐epistemic beliefs raise similar problems for a wide range of accounts of knowledge, and hence that they provide a powerful test for theories of knowledge.